Analisis Faktor-Faktor Yang Mempengaruhi Keterlambatan Pada Proyek Konstruksi Bangunan Gedung Pemerintah Di Kota Singkawang - -, Elkanady; Widodo, Slamet (Jurnal Teknik Sipil, 2020)
Infrastructure development through construction projects in the Singkawang City Government is inseparable from the problem of frequent delays in construction, there are even some construction projects that have not been completed, so that in the end it is very detrimental for the City Government of Singkawang and the people of Singkawang City as the end users of the construction project.Therefore, this study aims to determine the main factors causing work delays in building construction projects in the City Government of Singkawang and to determine the respective rankings of the factors causing work delays in building construction projects in Singkawang City Government.This study analyzes the factors that cause delays in building construction projects, whether they have an influence on project delays and how much influence each of these factors or variables has.  Keywords: Factors of Delay, Construction Projects, Ranking, Influence